Displacement and solidarity: An ethic of place‐making - Eckenwiler, Lisa (Bioethics, 2018)
Drawing on a conception of people as ‘ecological subjects’, creatures situated in specific social relations, locations, and material environments, I want to emphasize the importance of place and place‐making for basing, demonstrating, and forging future solidarity. Solidarity, as I will define it here, involves reaching out through moral imagination and responsive action across social and/or geographic distance and asymmetry to assist other people who are vulnerable, and to advance justice. Contained in the practice of solidarity are two core ‘enacted commitments’, first, to engaging our moral imaginations and recognizing others in need and, second, to responsive action. Recognizing the suffering of displacement and responding through place‐making should follow from even the most simplistic understanding of people as ‘implaced’. Recognition, furthermore, that places are created and sustained, transformed, or neglected in ways that foster or perpetuate inequities, including health inequities, generates responsibilities concerning place‐making. Place‐based interventions, on either count, should be principal and, indeed, prioritized ways of showing solidarity for the vulnerable and promoting justice. Where solidaristic relations do not prevail, place‐making can catalyze and nurture them, and over time advance justice. On the moral landscapes of bioethics, the terrain where care and health are or should be at the center of attention, an ethic of place and place‐making for those who have been displaced – patients, the elderly, urban populations, and asylum‐seekers, for instance – expresses and has rich potential for nurturing bonds of solidarity.